Pengembangan Modul Pencemaran Lingkungan Berbasis Islam-Sains untuk Siswa Madrasah Aliyah/MA - Dewi, Tisrin Maulina (Magister Pendidikan Biologi, Universitas Negeri Medan, 2017)
This study aims to determine: (1) The expedience degree of biology environmental pollution based Islamic-Science class X MA; (2) The responses of MA Biology teachers;Â and (3) The responses of students as to biology environmental pollution based Islamic-Science class X MA. This type of research is the development of research with product development model Borg and Gall, modified as needed. Data on quality of product development were collected by questionnaire. Data analyzed with descriptive quantitative and qualitative techniques. The results of this study showed that: (1) Validation of material expert is in very good criteria (88%); (2) Validation of learning design expert is in very good criteria (86%); (3) Assesment studies of biology teachers are in very helping criteria (3,4); (4) individual testing areÂ in good criteria (80%); (5) A small test group are in very good criteria (88%); Group confined field trials are in very good criteria (90%), so it can concluded that module environmental pollution class X MA based Islamic-Science is fit for use as a supporting for learning environmental pollution at school.